2019
DOI: 10.12788/jhm.3334
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Limited English Proficiency and Sepsis Mortality

Abstract: BACKGROUND: Limited English proficiency (LEP) has been implicated in poor health outcomes. Sepsis is a frequently fatal syndrome that is commonly encountered in hospital medicine. The impact of LEP on sepsis mortality is not currently known. OBJECTIVE: To determine the association between LEP and sepsis mortality. DESIGN: Retrospective cohort study. SETTING: 800-bed, tertiary care, academic medical center. PATIENTS: Electronic health record data were obtained for adults admitted to the hospital with sepsis bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 42 publications
0
38
1
Order By: Relevance
“…There have also been concerns that limitation of inperson family-provider contact to restrict virus transmission would negatively impact patients with limited English proficiency. 17,18 Our cohort analysis suggests that language preference was not associated with disproportionate code status reversal or delayed time to initial goals of care conversation, an outcome metric that may capture the impact of strained communication. This suggests that intensive care unit providers were able to establish ancillary communication methods including telephone and videoconferencing to engage families in goals of care conversations during the pandemic, with no substantial delay in time to first goals of care conversation as compared to prior literature.…”
Section: Discussionmentioning
confidence: 82%
“…There have also been concerns that limitation of inperson family-provider contact to restrict virus transmission would negatively impact patients with limited English proficiency. 17,18 Our cohort analysis suggests that language preference was not associated with disproportionate code status reversal or delayed time to initial goals of care conversation, an outcome metric that may capture the impact of strained communication. This suggests that intensive care unit providers were able to establish ancillary communication methods including telephone and videoconferencing to engage families in goals of care conversations during the pandemic, with no substantial delay in time to first goals of care conversation as compared to prior literature.…”
Section: Discussionmentioning
confidence: 82%
“…This observational cohort study provides novel insights regarding the duration of rehabilitation provided to older adults during a prolonged hospitalization for a range of diagnoses, and highlights large disparities in RD within a large safety‐net hospital that may contribute to differences in clinical and functional outcomes 25,33‐39 . We found that hospitalized older adults received about 1 hour of multidisciplinary rehabilitation per week.…”
Section: Discussionmentioning
confidence: 80%
“…We classified patients as having limited English proficiency (LEP) if in the electronic medical record (EMR), their preferred language for healthcare was a language other than English and if they self-identified as needing an interpreter. This definition was validated through chart review in a prior study conducted at the same institution 3 . In that study, compared to the chart reviewers’ assessment of English proficiency, the definition had a positive predictive value of 100%; thus, any misclassification in this study would err on the side of categorizing patients with LEP as EP.…”
Section: Methodsmentioning
confidence: 99%
“…1 These barriers are particularly problematic in the hospital, where patients with LEP are more likely to suffer adverse events, have higher mortality rates, and have higher readmission rates than English proficient (EP) patients. 2,3 While prior studies have documented in-hospital adverse events, the experience of patients with LEP during and after hospital discharge is not well understood.…”
Section: Introductionmentioning
confidence: 99%